2013
DOI: 10.1007/s11743-013-1534-5
|View full text |Cite
|
Sign up to set email alerts
|

Trends to Attain a Lower Interfacial Tension in a Revisited Pure Alkyl Polyethyleneglycol Surfactant–Alkane–Water Ternary System. Basic Concepts and Straightforward Guidelines for Improving Performance in Enhanced Oil Recovery Formulations

Abstract: Surfactant–oil–water systems exhibit a low interfacial tension minimum when the interactions between the adsorbed surfactant with water exactly coincide with its interactions with oil. This occurrence takes place at the so‐called optimum formulation, which was conceptually derived by Winsor in the 1950s and rendered by numerical correlations for enhanced oil recovery in the 1970s. The actual low value of the interfacial tension minimum has been found to increase or decrease with formulation variables and thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 45 publications
2
70
1
Order By: Relevance
“…Thus, the optimum concentration of SDS was considered to be 0.5 wt% for this system. According to Salager et al ([9], p. 199) ''surfactant-oilwater systems exhibit a low interfacial tension minimum when the interactions between the adsorbed surfactant with water exactly coincide with its interactions with oil…The actual low value of the interfacial tension minimum has been found to increase or decrease with formulation variables and …no general relationship have been reported up to now, probably because too many variables are involved in complex interactions'' [8].Therefore, the experimental observations for the specific system evaluated in this work indicates that the lowest interfacial tension (minimum IFT value) for the SDS-Stoney Creek Oil-Brine (2 wt% brine) system is 0.056 mN/m at the experimental conditions of this work. Figure 3 presents the IFT as a function of b-CD/SDS molar ratio, in which the IFT decreases as the b-CD/SDS molar ratio increases until an equimolar ratio is reached, after which the reverse process takes place, thus the IFT increases as the b-CD/SDS ratio is further increased.…”
Section: Interfacial Tension Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the optimum concentration of SDS was considered to be 0.5 wt% for this system. According to Salager et al ([9], p. 199) ''surfactant-oilwater systems exhibit a low interfacial tension minimum when the interactions between the adsorbed surfactant with water exactly coincide with its interactions with oil…The actual low value of the interfacial tension minimum has been found to increase or decrease with formulation variables and …no general relationship have been reported up to now, probably because too many variables are involved in complex interactions'' [8].Therefore, the experimental observations for the specific system evaluated in this work indicates that the lowest interfacial tension (minimum IFT value) for the SDS-Stoney Creek Oil-Brine (2 wt% brine) system is 0.056 mN/m at the experimental conditions of this work. Figure 3 presents the IFT as a function of b-CD/SDS molar ratio, in which the IFT decreases as the b-CD/SDS molar ratio increases until an equimolar ratio is reached, after which the reverse process takes place, thus the IFT increases as the b-CD/SDS ratio is further increased.…”
Section: Interfacial Tension Measurementsmentioning
confidence: 99%
“…The mechanism of oil recovery via surfactant flooding is the reduction of the interfacial tension (IFT) between the aqueous phase (brine) and crude oil to ultralow interfacial tension values. The values of IFT are commonly reduced from 30 mN/m (dyne/cm) to as low as 0.001 mN/m (dyne/ cm) or less, which are several orders of magnitude below the typical IFT values of brine-crude oil systems within oil reservoirs [3,[8][9][10].…”
Section: Introduction Surfactant Floodingmentioning
confidence: 99%
“…By separating the contributions of different formulation parameters, the HLD concept can define the surfactant characteristics with high accuracy, about ±0.1 units, which is much better than the usual ±2 unit approximation attainable by the HLB value [41]. According to the above concept, it has been recently shown that for pure n-alcohol ethoxylate-alkane-water systems, without salt and alcohol, the HLD values can be calculated by the following equation [44]:…”
Section: Interpretation Of Emulsification Observationsmentioning
confidence: 99%
“…On a pore scale, surfactants reduce the interfacial tension between oil and water to ultralow values, which decreases capillary forces and releases oil from the rock into the driving fluid. Therefore, under the condition of a high capillary number, oil droplets can be efficiently mobilized [1][2][3].…”
Section: Introductionmentioning
confidence: 99%